2020
DOI: 10.1039/d0ra03906c
|View full text |Cite
|
Sign up to set email alerts
|

The effect of post-deposition annealing conditions on structural and thermoelectric properties of sputtered copper oxide films

Abstract: This study reveals the interplay between the composition and thermoelectric performance of mixed copper oxide thin films, which can be finely adjusted by varying the annealing atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…It demonstrates a reduced level of resistance to the procedure of charge transfer. The electrode has stronger potentials for powerful ionic conductivity and outstanding capacitive responses due to its reduced diffusion path duration and reduced equivalent series and charge transfer resistances [61,62].…”
Section: Two Electrode Assemblymentioning
confidence: 99%
“…It demonstrates a reduced level of resistance to the procedure of charge transfer. The electrode has stronger potentials for powerful ionic conductivity and outstanding capacitive responses due to its reduced diffusion path duration and reduced equivalent series and charge transfer resistances [61,62].…”
Section: Two Electrode Assemblymentioning
confidence: 99%
“…The most wellknown stoichiometry for thermoelectric applications is that of CaMnO 3 , with zT values of 0.15 for 1173 K. [125] This value can be improved by doping with different rare-earth elements. Nevertheless, in the same work of Thiel et al, they reported tungsten doping, obtaining a zT value of 0.25 at 1223 K. [125] Cuprous oxide, Cu 2 O, has a Seebeck coefficient as high as 1050 µV•K −1 at temperatures of 923 K. [126] In the form of thinfilms, with both the copper oxides mixed in it, Seebeck values up to 204 µV•K −1 were reported, along with an electrical conductivity of 50 S•m −1 at room temperature, [127] but the thermal conductivity does not appear reported in those works, so in this case, there is still room for studying the material for thermoelectric applications.…”
Section: Earth-abundant Oxidesmentioning
confidence: 99%
“…The most commonly used are vapor chemical-based techniques, but also chemical synthesis such as sol-gel hydrolysis, solvothermal [151] or electrochemical methods, [113] such as Ti anodization, and hydrothermal synthesis are widely used for producing different oxides. Vapor deposition techniques such as atomic layer deposition, [152] sputtering, [127] molecular beam epitaxy, [153] or pulsed laser deposition [133,154] can also be used to form highly crystalline oxides. Finally, sintering methods such as SPS [140] or solid-state reactions [138] have also been used to form certain metal oxides…”
Section: Earth-abundant Oxidesmentioning
confidence: 99%
“…It has 12 phonon branches: four atoms in the primitive cell (four Cu-O molecules per unit cell and two CuO units in the primitive cell). A factor-group analysis gives the following zone-center modes [15]:…”
Section: Raman Spectroscopymentioning
confidence: 99%